2009
DOI: 10.1111/j.1541-0420.2009.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of Growth Curves Using Mixed Models Defined by Stochastic Differential Equations

Abstract: Growth curve data consist of repeated measurements of a continuous growth process over time in a population of individuals. These data are classically analyzed by nonlinear mixed models. However, the standard growth functions used in this context prescribe monotone increasing growth and can fail to model unexpected changes in growth rates. We propose to model these variations using stochastic differential equations (SDEs) that are deduced from the standard deterministic growth function by adding random variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 21 publications
0
59
0
1
Order By: Relevance
“…For instance, Donnet et al . () found that a stochastic differential equation (SDE) version of the Gompertz growth model is superior to its non‐linear deterministic mixed model counterpart, for prediction of the body weight of growing chickens. Donnet and Samson () reported similar findings from pharmacokinetic experiments and Whitaker et al .…”
Section: Introductionmentioning
confidence: 97%
“…For instance, Donnet et al . () found that a stochastic differential equation (SDE) version of the Gompertz growth model is superior to its non‐linear deterministic mixed model counterpart, for prediction of the body weight of growing chickens. Donnet and Samson () reported similar findings from pharmacokinetic experiments and Whitaker et al .…”
Section: Introductionmentioning
confidence: 97%
“…A similar approach has employed a mixed-effects modeling for growth curves resulting from the Gompertz model. 42 Using each point of peptide data separately rather than averaging the peptide data will allow us to estimate the variability due to the heavy-isotope labeling of peptides. In addition, we will extend the model to describe the turnover of proteins that are not in a steady-state condition.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches for estimating the curve parameters that specify a group of SDEs using observed data at discrete time points have been proposed [30]. Donnet et al [31] developed a Bayesian method to estimate SDE-based mixed model parameters using PK/PD data, typical of high sparsity and subject-dependent measure schedule. A review of the estimation of SDEs in PK/PD models is given by Donnet and Samson [21].…”
Section: Introductionmentioning
confidence: 99%